2018
DOI: 10.1111/bjd.16833
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of imaging strategy for an intensive follow‐up of patients with American Joint Committee on Cancer stage IIB , IIC and III malignant melanoma

Abstract: Six-monthly CT scan of the chest, abdomen and pelvis is a cost-effective technique for the early detection of metastases in the first 4 years of follow-up in patients with AJCC stage IIC and III melanoma, and in the first 3 years in patients with AJCC stage IIB melanoma. In addition, brain MRI has been shown to be cost-effective only in the first year of follow-up in patients with AJCC stage IIC and III melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…A main focus of discussion is whether surveillance CT will actually detect recurrences in a meaningful proportion of asymptomatic patients before those patients might prompt work‐up and detection by their provider. The detection of recurrences by surveillance CT scans has been reported to be between 24% and 59% when reviewing late stage II and stage III disease . Several more recent studies found that CT scans first detect at least half of systemic recurrences .…”
Section: Surveillance Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A main focus of discussion is whether surveillance CT will actually detect recurrences in a meaningful proportion of asymptomatic patients before those patients might prompt work‐up and detection by their provider. The detection of recurrences by surveillance CT scans has been reported to be between 24% and 59% when reviewing late stage II and stage III disease . Several more recent studies found that CT scans first detect at least half of systemic recurrences .…”
Section: Surveillance Modalitiesmentioning
confidence: 99%
“…This ranges to nearly 8% for a 20‐year old female patient when receiving a PET/CT every 6 months for 10 years . Although costly, Podlipnik et al concluded recently that 6‐monthly surveillance CT scans were cost‐effective in stages IIB, IIC, and III patients for the first 3 years after diagnosis. Of note, although uncommon, curable secondary malignancies may be incidentally discovered (reported 6% in a melanoma surveillance series with PET) during posttreatment serial imaging, which is an ancillary benefit …”
Section: Surveillance Modalitiesmentioning
confidence: 99%
“…[2][3][4] After the diagnosis of a primary melanoma, patients are enrolled in follow-up schedules depending on their risk of relapse, but due to its increasing prevalence, the workload and costs of surveillance programs have increased markedly. [5][6][7][8] Many surveillance strategies have been proposed, mainly based on initial AJCC clinical-pathological staging; [9][10][11] nevertheless, there are still many 'low-risk' melanoma patients who suffer relapses, resulting in high mortality. 9 In addition, approximately two thirds of patients whose melanoma will metastasize leading to death were initially sentinel lymph node biopsy (SLNB) negative (American Joint Committee on Cancer [AJCC] stages I and II).…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel lymph node biopsy and follow‐up protocols were carried out according to the institution's guidelines . Overall survival (OS) time was calculated from the date of diagnosis of the primary melanoma to the date of death by any cause or last follow‐up visit.…”
Section: Methodsmentioning
confidence: 99%
“…Sentinel lymph node biopsy and follow-up protocols were carried out according to the institution's guidelines. 26,27 Overall survival (OS) time was calculated from the date of diagnosis of the primary melanoma to the date of death by any cause or last follow-up visit. Melanoma-specific survival (MSS) was calculated from the time of diagnosis of the primary melanoma to the time of death by melanoma or the last followup visit.…”
Section: Cohort Descriptionmentioning
confidence: 99%